Socio-cultural acceptability of cadaver Transplantation in Iran - Mobasser, N; Zahmatkeshan, N; Farhadi, N; Nikeghbalian, S; Hasankhani, H (International Journal of Natural Sciences, 2012)
Organ transplantation is known to be a new and innovative treatment for patients with progressive organ failures. The present study investigates the current status of transplantation from cadaver along with its socio-cultural acceptability in Iran. The present study is a descriptive research in a systematic review method. Here, by investigating previously conducted researches in Iran during the period 2002- 2010, the status of transplantation from cadaver and its socio-cultural acceptability in Iran has been investigated. To collect the data, the access to Iranmedex website, the premier medical data center in Iran, was made possible using the related keywords. The obtained data indicate whereas there is an increase in the number of organ donations from cadaver, it is still low in comparison to other countries. The lack of consent from families of brain-dead patients is a major hurdle on the way of organ transplantation in Iran. In the cases of willingness to donate organs, the major effective factors were the deceaseds religious beliefs and prior tendency. In 66% of the cases, the donors families deemed organ donation phenomenon effective in alleviating the sorrow after the death of their beloved ones. The number of organ donation from cadaver in Iran is low contrary to other countries. It seems that general instructions to raise the knowledge on the subject and lay the foundation to increase the tendency towards posthumous organ donation are necessary. International Journal of Natural Sciences (2012), 2(3):63-66 DOI: http://dx.doi.org/10.3329/ijns.v2i3.12133